Transnational trailblazers of early cinema Sarah Bernhardt, Gabrielle Réjane, Mistinguett - Duckett, Victoria (Cinema cultures in contact, 2023)
A free ebook version of this title is available through Luminos, University of California Presss Open Access publishing program. Visit www.luminosoa.org to learn more. At the forefront of the entertainment industries of the late nineteenth and early twentieth centuries were singular actors: Sarah Bernhardt, Gabrielle Rjane, and Mistinguett. Talented and formidable women with global ambitions, these performers forged connections with audiences across the world while pioneering the use of film and theatrics to gain international renown. Transnational Trailblazers of Early Cinema traces how these women emerged from the Parisian periphery to become world-famous stars. Building upon extensive archival research in France, England, and the United States, Victoria Duckett argues that, through intrepid business prowess and the use of early multimedia to cultivate their celebrity image, these three artists strengthened ties between countries, continents, and cultures during pivotal years of change.